GPU-accelerated visualisation of ADS granular flow target model. (2015) - Tian, Yan-Shan; Zhou, Qingguo; Sun, Hong-Yu; Wu, Jiong; Zhang, Xun-Chao; Li, Kuan-Ching
This paper presents a discrete element method to handle particle collision detection and responses in transport simulation (the simulation of transport of protons and neutrons in granular flow target geometric model) based on GPUs. Discrete element method was adopted in the realisation of large-scale particle visualisation. The method simulates and solves edge detection, position judging, motion direction, calculation of the next collision point using GPU acceleration during the process of transport, and demonstrates the complete interaction process through OpenGL. Results show that the model presented exploits the acceleration of GPUs and has gained remarkable functional improvement compared with traditional method using solely CPUs. In addition, we used the MCNPX to calculate this model with high-speed proton bombardment. The distribution of power energies verifies that the granular flow target model is reliable and feasible.